Prospects of competitive team entrepreneurship in the Eastern Cape - Asoba, Samson Nambei; Mefi, Nteboheng Patricia (Journal of Ecohumanism, 2025)
The study is oriented to the need to strengthen economic activities in rural areas through team entrepreneurship. This is against the need to address structural inequalities and poverty levels in rural communities within the Eastern Cape Province. The perspective that team and collective entrepreneurial effort may be a relevant strategy to accelerate entrepreneurial activity in rural areas given the general position that the philosophy of collectivism is firmly entrenched in the South African rural society and team ventures may be more resilient and relevant as it allows the sharing use of material, intellectual and financial resources. The study adoption a qualitative research approach where data was collected through focus group discussions with some entrepreneurs in the Eastern Cape Province and data was analysed to establish central themes that inform prospects for team entrepreneurship. The results of the study showed that the prospects for the adoption of team entrepreneurship are weak due to institutional and structural entrepreneurial policies and strategies that are aligned to the sole entrepreneur perspective. Improving team entrepreneurship calls for context specific and community driven policies in entrepreneurship development. This would imply significant transformation of the South Africa entrepreneurial policy strategy. It is recommended that the South African entrepreneurial strategy should be reformed towards context focus and the promotion of localised values and culture systems such as ubuntu and collectivism in support of team entrepreneurship.